Tinjauan Teologis Terhadap Postmodernisme Dan Implikasinya Bagi Iman Kristen - Made Nopen Supriadi (Sekolah Tinggi Teologi Arastamar Bengkulu, 2020)
Times have changed, from pre-modern to modern, and now into postmodern times. The postmodern era is also followed by philosophical thinking from postmodernism. These philosophical thoughts have greatly influenced the lives of many people, who have also touched on aspects of the Christian faith. The principles of postmodernism are subjectivism, anti-history, perspective pluralism, and relativity. These principles have a negative influence on the principles of the Christian faith so that postmodernism is one of the challenges in the Christian faith. The challenge is that postmodernism is an objective anti-truth philosophy. So that it affects the lives of believers so that they remain faithful to reveal the final truth of the Christian faith, making Christian faith the only test tool against postmodernism and dismantling the falsity of postmodernism. Therefore this article was written to provide an understanding of postmodernism and its implications for the Christian faith so that many believers can provide anticipation in the postmodern era that is lived today.